Система визначення ризиків розвитку ПТСР під час дистанційного навчання з використанням згорткових нейронних мереж - Заброда, І. С. (ХНУРЕ, 2024)
This article considers the relevance and problematics of diagnosing PTSD in students who study with the help of distance learning in wartime. The experience of the state institution "Institute of Eye Diseases and Tissue Therapy named after V.P. Filatov of the National Academy of Medical Sciences of Ukraine" in diagnosing PTSD by means of eye movement is considered.
Keywords: дистанційне навчання; згорткова нейронна мережа